2006
DOI: 10.1111/j.1365-2257.2006.00844.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of platelet function and lack of response to epinephrine in pregnant women

Abstract: Summary Previous studies in healthy subjects have demonstrated a lack of response of platelets to epinephrine at a rate of 16–40% on an aggregometer. An association between the increased procoagulant factors during pregnancy and venous thromboembolism is known, and it has also been shown that prolactin levels increase platelet aggregation. We evaluated whether platelet functions in pregnant women and also assessed the lack of response to epinephrine during this period. We compared 27 healthy and volunteering p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…Previous studies reported no relationship between the lack of response to Epi and age or gender. 2,6,8,9 Considering the distinguished military institution from which the participants were selected and the health controls routinely conducted in the institution, the fact that the lack of response to Epi was low make us think that there may be a relationship between a health parameter that we did not notice and the lack of response to Epi.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies reported no relationship between the lack of response to Epi and age or gender. 2,6,8,9 Considering the distinguished military institution from which the participants were selected and the health controls routinely conducted in the institution, the fact that the lack of response to Epi was low make us think that there may be a relationship between a health parameter that we did not notice and the lack of response to Epi.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, final Epi concentrations varied between 10 and 300 mmol/L. [2][3][4][5][6][7][8][9] The duration of the transition from primary aggregation to secondary aggregation for the Epi-induced aggregation response may show some interpersonal variations. It was indicated that in pregnant women the lack of response to Epi was not observed; this may be due to a late-rising response to Epi.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The association of impaired platelet function in pregnant Gaucher patients with an increased risk of peripartum bleeding has not been previously reported. On the contrary, Sagdilek et al (18) have demonstrated platelet function to be preserved in normal pregnancy when compared with non-pregnant controls, while other authors have shown platelet activation during specific pregnancy-related conditions such as preeclampsia (19,20) and pregnancy-induced hypertension (21).…”
Section: P-valuementioning
confidence: 95%
“…Moreover, the reported results, obtained in a potentially hypercoagulable state, are applicable to future pregnancies only and should not be relied upon in cases of future surgical procedures in these patients. The lack of normal pregnancy controls for CPA studies is another flaw, yet since other studies have reported improved whole blood platelet function in pregnancy (18)(19)(20)(21), the use of normal population controls (whose whole blood platelet aggregation may be even lower than anticipated for normal pregnancy controls) as comparator for the Gaucher cohort, should not have affected our study's results and conclusion.…”
Section: P-valuementioning
confidence: 99%